2010
DOI: 10.1002/mawe.201000687
|View full text |Cite
|
Sign up to set email alerts
|

Resistance spot welding and weldbonding of advanced high strength steels

Abstract: The resistance spot welding procedure is one of the most important joining techniques in lightweight car body shell mass production. Especially for newly developed high strength multiphase steels, also called advanced high strength steels (AHSS), and ultra high strength steels (UHSS), this joining technique has more advantages than other thermal and mechanical joining procedures for thin steel sheets. Additionally, the technique of adhesive bonding and its combination with the technique of resistance spot weld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…It also improves the corrosion, noise resistance and joint stiffness [67]. Some studies related to microstructures and mechanical properties of WB joints have been reported [31,32,68,69]. Chang et al [31] studied a computational model and the stress field characteristics of WB joints for a car body steel sheet and observed a serious stress concentration existing at the edge of the weld spot in the spotwelded joints, and it could be removed or reduced by the application of adhesives.…”
Section: Weld-bonding Processmentioning
confidence: 99%
“…It also improves the corrosion, noise resistance and joint stiffness [67]. Some studies related to microstructures and mechanical properties of WB joints have been reported [31,32,68,69]. Chang et al [31] studied a computational model and the stress field characteristics of WB joints for a car body steel sheet and observed a serious stress concentration existing at the edge of the weld spot in the spotwelded joints, and it could be removed or reduced by the application of adhesives.…”
Section: Weld-bonding Processmentioning
confidence: 99%
“…It also improves the corrosion, noise resistance and joint stiffness [67]. Some studies related to microstructures and mechanical properties of WB joints have been reported [31,32,68,69]. Chang et al [31] studied a computational model and the stress field characteristics of WB joints for a car body steel sheet and observed a serious stress concentration existing at the edge of the weld spot in the spotwelded joints, and it could be removed or reduced by the application of adhesives.…”
Section: Weld-bonding Processmentioning
confidence: 99%
“…Thermally, the RSW process can be described by the general electro-kinetic equation, as stated in (1), which adds a Joule heating term to the commonly used general heat equation.…”
Section: Thermo-electrical Modelmentioning
confidence: 99%
“…An efficient solution to meet such demands is the introduction of high strength (HSS) and ultra high strength (UHSS, sometimes also referred to as advanced high strength steels, AHSS) in body-in-white components. While higher strength materials effectively enables reduction of car weight, the material behavior of HSS and UHSS, due to their metallurgy and alloying elements, also imposes challenges for joining in manufacturing [1].…”
Section: Introductionmentioning
confidence: 99%